1988
DOI: 10.1136/gut.29.6.795
|View full text |Cite
|
Sign up to set email alerts
|

Attachment of Giardia lamblia to rat intestinal epithelial cells.

Abstract: SUMMARY The human enteric protozoan, Giardia lamblia, has surface membrane lectin activity which mediates parasite adherence to erythrocytes. To determine whether an intestinal binding site exists for this lectin we have studied the interaction in vitro between axenically cultured Giardia trophozoites and isolated rat intestinal epithelial cells. Scanning electron microscopy showed that Giardia attached to the apical microvillus membrane and basolateral membrane of rat enterocytes. Any location on the parasite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0
3

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 19 publications
0
39
0
3
Order By: Relevance
“…" Preliminary experiments showed that the preincubation of Caco-2 cells with suspensions of L. johnsonii La1 did not inhibit the complex adhesion of trophozoites to cell monolayers (data not shown). This interaction involves the ventral disk, several contractile elements, and hydrodynamic and mechanical forces, as well as lectin-binding factors (18,21,24,25). The possibility remained that if an antagonistic effect of the bacteria against the parasite existed, it could result from the release of bacterial metabolites or products more than a competitive exclusion or steric hindrance (3).…”
Section: Discussionmentioning
confidence: 99%
“…" Preliminary experiments showed that the preincubation of Caco-2 cells with suspensions of L. johnsonii La1 did not inhibit the complex adhesion of trophozoites to cell monolayers (data not shown). This interaction involves the ventral disk, several contractile elements, and hydrodynamic and mechanical forces, as well as lectin-binding factors (18,21,24,25). The possibility remained that if an antagonistic effect of the bacteria against the parasite existed, it could result from the release of bacterial metabolites or products more than a competitive exclusion or steric hindrance (3).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that viruses [2], bacteria, bacterial toxins [3], and protozoa [4] specifically recognize and bind to cell-surface carbohydrates and that this interaction is necessary to cause an infection or produce a toxic effect. Thus, it is likely that alterations in glycosylation of the microvillus surface may influence the expression of receptors for regulation of cell growth, differentiation, and for colonization of enteric pathogens in the small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Using their flagella and ventral disc, trophozoites released in the upper part of the small intestine move to the microvillus-covered surface of the duodenum and jejunum, where they attach themselves (88,116), and play a role in the onset of the pathology (22,34,124). The suction force created by this mode of attachment may damage the microvilli and interfere with the process of food absorption (88,116). Eventually, the rapid multiplication of the trophozoites by binary fission creates a physical barrier between the intestinal epithelial cells and the lumen of the intestine, interfering with the process of absorption of nutrients.…”
Section: Giardiasismentioning
confidence: 99%